2016
DOI: 10.3390/ijms17111820
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Carbonic Anhydrase I in Motor Neurons and Alterations in ALS

Abstract: Carbonic anhydrase I (CA1) is the cytosolic isoform of mammalian α-CA family members which are responsible for maintaining pH homeostasis in the physiology and pathology of organisms. A subset of CA isoforms are known to be expressed and function in the central nervous system (CNS). CA1 has not been extensively characterized in the CNS. In this study, we demonstrate that CA1 is expressed in the motor neurons in human spinal cord. Unexpectedly, a subpopulation of CA1 appears to be associated with endoplasmic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…Our study for the irst time characterized a novel ly model of motor neuron toxicity that might be relevant to ALS. Previously discovered human CA1 whose levels were shown to be increased in the spinal cord of ALS patients [4], has now been demonstrated that when overexpressed in ly motor neurons is also toxic (Figure 2a & 2d). Among the established Drosophila models of ALS-linked genes, 5 molecules including SOD1, TDP-43, FUS and PFN1, when their wild-type human proteins were overexpressed in ly neurons caused toxicity [31,32,24].…”
Section: Conclusion and Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Our study for the irst time characterized a novel ly model of motor neuron toxicity that might be relevant to ALS. Previously discovered human CA1 whose levels were shown to be increased in the spinal cord of ALS patients [4], has now been demonstrated that when overexpressed in ly motor neurons is also toxic (Figure 2a & 2d). Among the established Drosophila models of ALS-linked genes, 5 molecules including SOD1, TDP-43, FUS and PFN1, when their wild-type human proteins were overexpressed in ly neurons caused toxicity [31,32,24].…”
Section: Conclusion and Discussionmentioning
confidence: 89%
“…The mechanisms of ALS pathogenesis are complex involving many players and pathways [3]. Recently, it was reported that human carbonic anhydrase I (hCA1) might be a player in ALS pathology as its levels were increased in spinal cord motor neurons of ALS patients including SALS and FALS [4]. Carbonic anhydrases (CAs) catalyze the reversible conversion from carbon dioxide and water to bicarbonate and proton which is the most essential and fundamental process in cellular metabolisms [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino alcohols 1–16 were here assayed for their activating properties of 4 catalytically active and physiologically relevant hCA isoforms expressed in human brain, that are: the cytosolic hCA I, II, and VII, and the membrane associated hCA IV 58 . In the CNS context, hCA I is expressed in the motor neurons in human spinal cord 59 . The physiologically dominant isoform hCA II is located both in the choroid plexus, and in oligodendrocytes, myelinated tracts, astrocytes and myelin sheaths in the vertebrates brain 60 .…”
Section: Resultsmentioning
confidence: 99%
“…Our genetic analyses found a strong pQTL for carbonic anhydrase IV, which is a target for Acetazolamide. Several studies have reported that the expression of Carbonic Anhydrase IV is altered in the motor neurons of Amyotrophic lateral sclerosis patients 48,49 . Acetazolamide is a carbonic anhydrase inhibitor 50 , used to treat glaucoma, epilepsy and altitude sickness 51 .…”
Section: Mendelian Randomization To Identify Novel Biomarkers and Drumentioning
confidence: 99%